2011
DOI: 10.4236/ojog.2011.14040
|View full text |Cite
|
Sign up to set email alerts
|

Effect of maternal alcohol consumption on gestational diabetes detection and mother-infant’s outcomes in Kinshasa, DR Congo

Abstract: Objectives: Since it has been suggested that moderate alcohol drinking would increase insulin sensitivity, which could benefit Gestational Diabetes Mellitus (GDM), the study aimed at evaluating alcohol consumption during pregnancy, and seeing whether this consumption influences GDM detection and maternal/perinatal outcomes. Study design: Women with already known diabetes and those with multiple pregnancy were excluded. All other pregnant women attending antenatal care unit of the university clinics, Kinshasa, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 14 publications
2
10
1
Order By: Relevance
“…The prevalence of alcohol consumption during pregnancy among the general population in the 25 identified studies ranged from 2.5% (Nigeria) to 32.5% (Democratic Republic of the Congo) (Table ). Five studies reported the prevalence of binge drinking during pregnancy among the general population, which ranged from 3.8% (South Africa) to 25.4% (Democratic Republic of the Congo) (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of alcohol consumption during pregnancy among the general population in the 25 identified studies ranged from 2.5% (Nigeria) to 32.5% (Democratic Republic of the Congo) (Table ). Five studies reported the prevalence of binge drinking during pregnancy among the general population, which ranged from 3.8% (South Africa) to 25.4% (Democratic Republic of the Congo) (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The percent of women consuming alcohol during pregnancy has been reported as a serious problem in other countries, such as 32.5% in Congo [ 31 ], 4.4% in India [ 32 ]. A study in Korea [ 33 ] suggests that women who drink alcohol may have an increased risk of persistent HPV.…”
Section: Discussionmentioning
confidence: 99%
“…The present day lifestyle, which primarily includes carbohydrate rich diet leading to obesity, is considered to be one of the major causes of this disease. Risk factors including maternal lifestyle, pre-pregnancy body mass index (BMI) [6], advancing age [7], abdominal circumference, smoking [8], alcohol consumption [9], history of Polycystic Ovarian Syndrome (PCOS) [10], use of anti-psychotics [11], exposure to air pollutants [12] and perfluorochemicals [13] during pregnancy are known to contribute towards disease progression. GDM complicates pregnancy by affecting both neonatal growth and maternal health.…”
Section: Introductionmentioning
confidence: 99%